Sosialisasi Pendidikan Anti Korupsi Sebagai Upaya Pencegahan Perilaku Korupsi Pada Siswa Kelas 5 Di SDN 8 Teluk Pandan Kabupaten Pesawaran - Arizal Eka Putra; Arinie Izzataqie Latifa; Ika Ardiyanti; Indriani Lestari; Tomi Andriko; Cahya Permata Sari (Jurnal Nusantara Berbakti, 2023)
Corruption can be defined as bad habitual behavior and is a common phenomenon in society. This concern arises because the perpetrators of corruption exist in both government and private organizations and may also involve leaders of organizations who are role models for the younger generation. One of the efforts to reduce the increase in corruption cases is to focus on the legal aspect. However, there have not been many preventive efforts through education that have the potential to eradicate the "culture of corruption". Anti-corruption education is a preventive effort to increase self-awareness and integrity in the face of corrupt practices. The purpose of this study is to determine whether anti-corruption education can develop students' sensitivity and awareness of corruption issues. The research method is to combine collective self-reflective action research with student-centered learning, conducted in small groups, and realized through critical reflective actions of group members as individuals, and measure the learning outcomes. The participants in this study amounted to 25 students in one class. The results obtained show that students are able to identify corrupt practices based on individual and collective experiences. Documented student corruption includes cheating, tardiness and fraud. Participants were also able to identify the impact of corrupt practices on individuals and (groups). Participants realized that corruption can create a "domino effect" of corrupt behavior over time. At the reflection stage, participants revealed the existence of integrity values in the form of honesty, responsibility, consistency of attitudes and behavior, and religious values that are believed to prevent corrupt practices. Activities carried out in the form of socialization as a form of change in the management of student organizations that are clean and anti-corruption.